What Encourages Sun Protection among Outdoor Workers from Four Industries - Janda, Monika; Stoneham, Melissa; Youl, Philippa; Crane, Phil; Sendall, Marguerite; Tenkate, Thomas; Kimlin, Michael (Japan Society for Occupational Health, 2014)
Objectives: We aimed to identify current practice of sun protection and factors associated with effective use in four outdoor worker industries in Queensland, Australia. Methods: Workplaces in four industries with a high proportion of outdoor workers (building/construction, rural/farming, local government, and public sector industries) were identified using an online telephone directory, screened for eligibility, and invited to participant via mail (n=15, recruitment rate 37%). A convenience sample of workers were recruited within each workplace (n=162). Workplaces’ sun protective policies and procedures were identified using interviews and policy analysis with workplace representatives, and discussion groups and computer-assisted telephone interviews with workers. Personal characteristics and sun protection knowledge, attitudes and behaviors were collated and analysed. Results: Just over half the workplaces had an existing policy which referred to sun protection (58%), and most provided at least some personal protective equipment (PPE), but few scheduled work outside peak sun hours (43%) or provided skin checks (21%). Several worker and workplace characteristics were associated with greater sun protection behaviour among workers, including having received education on the use of PPE (p<0.001), being concerned about being in the sun (p=0.002); and working in a 2014 smaller workplace (p=0.035). Conclusions: Uptake of sun protection by outdoor workers is affected by a complex interplay of both workplace and personal factors, and there is a need for effective strategies targeting both the workplace environment and workers’ knowledge, attitudes and behaviors to decrease harmful sun exposure further.